Public Participation in Health Policy Making: A Bibliometric Review of Scientific Publications - Judijanto, Loso; Saripudin, Risman; Andarmoyo, Sulistyo (Westscience Press, 2024)
Public participation in health policy-making is a vital component for fostering equity, transparency, and inclusivity in health systems worldwide. This study presents a bibliometric analysis of scientific publications to explore the research landscape on public participation in health policy-making. Using data from Scopus and Web of Science, the analysis identified key themes, influential contributors, and emerging trends. The findings reveal a growing emphasis on patient-centered care, governance frameworks, community health interventions, and the role of data and digital technologies. Prominent themes include the inclusion of vulnerable populations, such as women, children, and individuals with disabilities, as well as the integration of public input during health crises like the COVID-19 pandemic. Despite progress, challenges such as power imbalances, tokenistic participation, and the digital divide persist. This study highlights the importance of institutional frameworks, investments in data infrastructure, and digital tools to enhance participatory practices. Recommendations for future research include examining the long-term impact of participation, addressing gaps in low- and middle-income countries, and exploring the intersection of public engagement and technology. By synthesizing existing knowledge, this study contributes to advancing theory and practice in participatory health policy-making.